2007
DOI: 10.1097/01.sla.0000242716.66878.23
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic Cholelithiasis in Children With Sickle Cell Disease

Abstract: Elective LC should be the gold standard in children with SCD and asymptomatic cholelithiasis to prevent the potential complications of biliary colics, acute cholecystitis, and choledocholithiasis, which lead to major risks, discomfort, and longer hospital stay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
49
1
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(57 citation statements)
references
References 15 publications
3
49
1
4
Order By: Relevance
“…Some authors believe that it is indicated only in patients with comorbidities, particularly hemolytic anemias [12]. In the present series, we observed that significant proportion of all patients (25.1%) developed complications related to the presence of gallstones (eg, ACC, pancreatitis, choledocolithiasis), and the complication was the first sign of cholelithiasis.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…Some authors believe that it is indicated only in patients with comorbidities, particularly hemolytic anemias [12]. In the present series, we observed that significant proportion of all patients (25.1%) developed complications related to the presence of gallstones (eg, ACC, pancreatitis, choledocolithiasis), and the complication was the first sign of cholelithiasis.…”
Section: Discussionsupporting
confidence: 49%
“…In another publication, 10 of 14 initially asymptomatic patients with sickle cell disease became symptomatic and required surgery. In addition, the operative time, morbidity rate, and postoperative stay were greater among symptomatic patients who underwent cholecystectomy than in those who underwent the surgery when asymptomatic [12]. Another argument is that the presence of gallstones is a major risk factor for carcinoma of the gallbladder [13].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, biliary complications often precipitate veno-occlusive crises. Also, emergency surgery for complications is associated with significantly higher morbidity, mortality and increased hospital stay [25]. Elective, prophylactic cholecystectomy is thus recommended on diagnosis of GS before development of symptoms or complications.…”
Section: Special Subgroupsmentioning
confidence: 99%
“…However, Koduri et al reported that silent AVN occurred in 41% children aged 4-28 years with the spine and shoulder being involved in 27% and 28% cases, respectively [18]. This indicates that there is an underestimation of AVN prevalence in children because of asymptomatic AVN or insensitive AVN investigation by using radiography [19]. Earlier studies on AVN prevalence in patients with SCD were grossly underestimated, particularly, since 47% and 79% patients with hip and shoulder disease, respectively had no symptoms at the diagnosis time [20] for that reason bone scintigraphy is recommended to detect the silent and the multifocal AVN [21].…”
Section: Effectmentioning
confidence: 82%